The first Taeniolinum from the Andes Mountains and Colombia (Chilopoda: Geophilomorpha) - Tulande-M, Esteban; Prado, César Camilo; Triana, Hernán Darío (Zootaxa, 2018)
Taeniolinum neusicus sp. n. is described based on 148 specimens collected at the eastern Colombian Andes. Detailed data on environmental and biological preferences are included in the description. The validity of characters such as the number of labral teeth and the clypeal setae to separate Taeniolinum species is also evaluated.